If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6d + 22d + 12 = 0 Reorder the terms: 12 + 6d + 22d = 0 Combine like terms: 6d + 22d = 28d 12 + 28d = 0 Solving 12 + 28d = 0 Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 28d = 0 + -12 Combine like terms: 12 + -12 = 0 0 + 28d = 0 + -12 28d = 0 + -12 Combine like terms: 0 + -12 = -12 28d = -12 Divide each side by '28'. d = -0.4285714286 Simplifying d = -0.4285714286
| 3056890000-15000000x=2085000000+55000000x | | .50n=17 | | 10x+6=6x+7 | | 4x-10=5x-20 | | 16y+11y^2=12 | | 4(x+2)-3=2x+1 | | 5-3(4-2b)=4(b-3) | | 19-20b=18 | | 3x-(x+1)=41 | | 16n=5n | | 5x-12=4-6x | | -2(-3x)=8x+2x | | -37=3-8x | | 19x=49-10 | | 6x-4-3x=20 | | (3a+7)(2a-5)= | | 4x^2+47x+70=0 | | 10(x+.50)=3x+5+7x | | (-19)*y=1900 | | 36x=8x | | 4x+8x=12-10 | | x^3-5x^2+12=0 | | 5+-11n=24 | | (12)(-5)n=0 | | 42=-29(y+5) | | -7(y+4)-6y= | | X^2-7x=-144 | | 2x+x+4+2=3(x+2) | | 49=7f | | b+5=-2b-3 | | 7+2(x-6)=-3+2x(x-1) | | 2(y-4)=-3(y+2)-8 |